Camels and cattle respond differently in milk phenol excretion and milk fatty acid profile to free ranging conditions in East-African rangelands - Leparmarai, Paul Taipa; Kunz, Carmen; Mwangi, David Miano; Gluecks, Ilona V.; Kreuzer, Michael; Marquardt, Svenja (Elsevier, 2021)
Camels are getting increasingly important for pastoral livestock systems in arid and semi-arid rangelands of East Africa that are adversely affected by climate change. Cattle are more susceptible to drought than camels and rely on grass, while camels are primarily browsers. Diet selection can influence the quality of the milk, especially of the milk fat. Little is known about differences in milk fatty acid profile of camels compared to cattle, especially under free-grazing conditions. Camels and two cattle types were compared on Kenyan rangelands in a rainy season and a transition period. Seventy-two lactating animals (12 per animal type per season each) were used. Half of each group received a urea-molasses supplement at night. Intakes of nutrients and phenols were estimated through scan sampling. Milk was collected at the end of each season and analyzed for phenols and fatty acids. Phenol intakes varied between seasons in cattle but not in camels. Different from animal type, season had an effect on milk phenol concentration. Phenol excretion with the milk of cattle correlated with phenol intake. Proportions of mono- and polyunsaturated fatty acids were higher in camel milk than cattle milk. Cattle milk contained more conjugated linoleic acids than camel milk in the rainy season. Proportions of oleic, linoleic, α-linolenic and eicosapentaenoic acid were higher, whereas n-6-to-n-3 fatty acid ratio was lower in camel milk than cattle milk. Camels may have developed control mechanisms limiting adverse effects and transfer of phenols to milk in response to their higher intake of phenol-rich browse. In conclusion, camel milk seems to be more beneficial for human health and nutrition than cattle milk by its characteristic fatty acid profile. This can be another motivation for switching from cattle to camels in arid/semi-arid areas affected by climate change.